KNOWLEDGE, ATTITUDE, AND PRACTICE REGARDING IMMUNIZATION AMONG MOTHERS OF INFANT AND PRESCHOOL CHILDREN AT A TERTIARY CARE HOSPITAL, IN KARACHI. - KHAN , M; AKBER , JU; SOHRAB , S; KHAN , AH; HAQ , MHU; ALI , AA (Biological and Clinical Sciences Research Journal, 2024)
The objective of this research was to determine the knowledge, attitude, and practice of mothers of infant and preschool children regarding immunization. The study will be conducted at a tertiary care hospital in Karachi, and a total of 119 people will be recruited for KAP research. The mothers’ level of education, beliefs, and behaviors will be assessed along with factors such as a child’s age, gender, place of birth, number of siblings, marital status, educational level, employment status, and monthly income. The principal investigator will gather information using a self-designed questionnaire that includes questions on demographics and immunization-related knowledge. The results of the study indicate that 68.9% of the mothers had knowledge of immunization, whereas 31.1% did not. In addition, 68.1% of the mothers were aware of the Expanded Program on Immunization (EPI), while 31.9% were not. Regarding knowledge of the EPI 1st dose, 69.7% of the mothers had information about it, while 30.3% did not. Only 28.6% of the respondents had knowledge of diseases that could occur in the absence of vaccination, whereas 71.4% did not. In terms of specific diseases, 5.9% were aware of diphtheria, 5.9% of polio, 5% of tetanus, and 11.8% of influenza. However, 71.4% of the respondents did not have knowledge of diseases that could occur in the absence of vaccination. Furthermore, 35.3% of the parents expressed fear of immunization for their children, while 64.7% did not. Among those who had fears, 52.9% believed that there was no benefit to immunization, and 47.1% were concerned about harm to their children. In conclusion, the study found that more than half of the mothers who expressed fear of immunization did so because they believed there was no benefit. This highlights the need for more education and awareness campaigns to help parents understand the importance of immunization in preventing diseases and keeping their children healthy.